Precipitation of Zn(II)-Pyrazinamide Complex from Ethanol Solution as an Antibacterial Candidate based on Transitional Metal Complex Compounds - Adiba, Naila Azmi; Purwonugroho, Danar; Prananto, Yuniar Ponco (Indonesian Green Technology Journal, 2024)
The Zn(II)-pyrazinamide complex compound is currently being developed as an antibacterial agent. To obtain the Zn(II)-pyrazinamide complex effectively, many factors must be considered, including the type of zinc(II) salt and the mole ratio. The aim of this research is to examine the influence of the type of zinc(II) salt and the mole ratio in the precipitation of the Zn(II)-pyrazinamide complex to obtain efficient results. The Zn(II)-pyrazinamide complex was synthesized using a direct mixing technique in ethanol solution with metal:ligand mole ratios of 1:2 and 1:4 and with types of zinc(II) salts, namely acetate, chloride, and nitrate. Based on the research results, the anion of the zinc(II) salt leads to the precipitation of the complex while the metal:ligand mole ratio leads to the resulting yield. An efficient synthesis condition to obtain the Zn(II)-pyrazinamide complex is to use ZnCl2 salt and a mole ratio of 1:4. Experimental data also shows that the Zn(II)-pyrazinamide complex precipitate melts at a temperature of 234oC, while infrared spectroscopy analysis shows the characteristic carbonyl and amide groups of pyrazinamide. Meanwhile, powder-XRD analysis showed that the resulting complex had a different structure than that previously reported.